2019
DOI: 10.1103/physrevb.100.155430
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric transport coefficients of a Dirac electron gas in high magnetic fields

Abstract: We study the thermoelectric transport properties of a three-dimensional massive relativistic fermion gas with screened Coulomb impurities in high magnetic fields where only the lowest Landau levels contribute to the transport. Our results can be applied to experimental results of gapless and gapped Dirac materials. We focus on the effects of the mass term and we show the main differences that arise compared to the massless Dirac fermions. The different behavior is shown to be relevant at higher magnetic fields… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Recent theoretical works suggested the possibility of record-high thermoelectric conversion efficiency in semiconductors and semimetals under a quantizing magnetic field [3,4], where the thermoelectric response is directly related to entropy [5][6][7][8]. Based on this relation, it is found that the thermopower of three-dimensional (3D) Dirac and Weyl materials in the quantum limit increases unboundedly with magnetic field [3,[9][10][11][12]. Very recently, it is shown that two-dimensional (2D) quantum Hall systems can reach a thermoelectric figure of merit on the order of unity down to low temperature (T ), as a consequence of the thermal entropy from the massive Landau level (LL) degeneracy [4].…”
mentioning
confidence: 99%
“…Recent theoretical works suggested the possibility of record-high thermoelectric conversion efficiency in semiconductors and semimetals under a quantizing magnetic field [3,4], where the thermoelectric response is directly related to entropy [5][6][7][8]. Based on this relation, it is found that the thermopower of three-dimensional (3D) Dirac and Weyl materials in the quantum limit increases unboundedly with magnetic field [3,[9][10][11][12]. Very recently, it is shown that two-dimensional (2D) quantum Hall systems can reach a thermoelectric figure of merit on the order of unity down to low temperature (T ), as a consequence of the thermal entropy from the massive Landau level (LL) degeneracy [4].…”
mentioning
confidence: 99%
“…Moreover, the recent theoretical studies prove that an artificial superlattice with a high layer barrier periodic potential is an ideal platform for realizing 3D QHE [32]. On the other hand, the thermoelectric transport has stimulated strong research interest in recent years [33][34][35][36][37]. However, despite a numerical study based on the Kubo formula [37], concise and easily manipulable formulas and systematic theoretical investigation of the thermoelectric transport coefficients in a 3D QHE system are still highly desirable.…”
mentioning
confidence: 99%